2016
DOI: 10.1515/libri-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Value of Book Loans – The Case of the Municipal Library of Prague

Abstract: In recent years, the value of public library services has tended to be evaluated using the contingent valuation method. This is able to reveal readers’ hidden preferences. However, it appears that the total value of a public library as expressed by one number leads to a methodological bias related to the difficulty of assessing the value of one standard book loan. Moreover, this approach does not reflect the needs of public libraries’ management. Therefore, this study focuses on a detailed investigation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Different groups of e-book readers create demand, and the volume of this demand is influenced by various factors which need to be analysed according to each group's willingness to request access to a printed book or e-book. A number of studies have addressed the WTP for the provision of books (Fujiwara et al, 2019;Lee and Chung, 2012;Stejskal et al, 2016) and e-books (Ahmad and Brogan, 2016;Min et al, 2011;Stejskal and Hajek, 2015). All studies concluded that regular readers (e.g.…”
Section: El 394mentioning
confidence: 99%
“…Different groups of e-book readers create demand, and the volume of this demand is influenced by various factors which need to be analysed according to each group's willingness to request access to a printed book or e-book. A number of studies have addressed the WTP for the provision of books (Fujiwara et al, 2019;Lee and Chung, 2012;Stejskal et al, 2016) and e-books (Ahmad and Brogan, 2016;Min et al, 2011;Stejskal and Hajek, 2015). All studies concluded that regular readers (e.g.…”
Section: El 394mentioning
confidence: 99%
“…The research of Stejskal et al (2016) focused on a detailed investigation of the most important public library service-book loans. For this purpose, they have used statistical models to identify the significant determinants of WTP for book loans and WTP for purchasing books.…”
Section: Evaluation Of a Library's Economic Valuementioning
confidence: 99%